Enhanced columnar mesophase range through distortions in arene cores. (24th March 2017) - Vollbrecht, Joachim; Wiebeler, Christian; Schumacher, Stefan; Bock, Harald; Kitzerow, Heinz
ABSTRACT: The influence of sterically hindered functional groups on liquid crystalline properties is studied for two series of perylene-3, 4, 9, 10-tetracarboxylic tetraesters and diimides. The results indicate an enhanced mesophase range owing to the decrease of the melting temperature. The role of axial chirality is also studied by comparing the liquid crystalline properties of unilaterally and bilaterally extended perylene derivatives. In summary, both bulky substituents and distortion of the polycyclic aromatic core can lead to an enlarged temperature range of columnar mesophases.